MILK PRODUCTION AND BUSINESS ANALYSIS ON DAIRY CATTLE AFFECTED BY PMK IN “KAMPOENG TERNAK” SIDOARJO LIVESTOCK: A LITERATURE REVIEW - Winda Ayu Puteri Sumartono; Sri Hidanah; Ira Sari Yudaniayanti; Widya Paramita; Moh Anam Al Arif; Imam Mustofa (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
mineral superboosters and concentrating immunoboosters in the feed. This research was conducted on the smallholder dairy cattle in "Kampoeng Ternak," Taman District, Sidoarjo, for 42 days. The material used was 18 Friesian Holstein (FH) dairy cattle suffering from FMD and decreased milk production. This research was carried out experimentally with three treatments: P0 (treatment injected multivitamins 10 ml + antibiotic long-acting 20 ml), P1 (treatment injected multivitamins 10 ml + antibiotic long-acting 20 ml and mineral super booster 40 grams), and P2 (10 ml treatment injected multivitamins + 20 ml long-acting antibiotics, adding 40-gram mineral super booster and 800-gram concentrate immunobooster). The data collected in this study is feed consumption, milk production, and profit analysis of business in the farm. The data were calculated and analyzed using anova. This literature review aims to describe adding mineral supplements to FH dairy cattle suffering from foot and mouth disease (FMD) as an alternative because it can increase milk production.